Analysis of Clinicopathological Parameters and Ki 67 Immunoexpression in Urothelial Neoplasms of Bladder - Chandrasekar, Megala; V, Saranya; B, Surekha (Annals of Pathology and Laboratory Medicine, 2020)
Background: Mitotic count is one of the most important determinant of proliferative capacity of any tumour. Immunohistochemical expression of ki 67 is an alternative and effective way of determining the growth fraction. This study was conducted to assess the expression of Ki 67 proliferative marker in bladder urothelial tumors, and to correlate proliferative markers with histopathological grading & staging, thereby helps in identifying high risk patients for disease progression and recurrence who may thus benefit from perioperative systemic chemotherapy. Methods: This study was conducted in department of pathology in collaboration with department of urology in the period of I year from March 2018-March 2019. Results was evaluated on paraffin embedded tissues of bladder neoplasm specimens by immunohistochemical methods and correlated with clinical parameters. Result: In present study, high grade tumours have over expression of Ki 67 and graded as 3+ and 4+. Low grade tumours have low expression and have grades 1+and 2+. Out of 30 cases,40% (12 cases) show 4+ and 27% show (8 cases)3+, both being high grade tumors. Whereas, 27% (8 cases) have 1+ and 7% (2 cases) have 2+, both being low grade tumours). p value is highly significant which is p<0.001. Conclusion: Expression of Ki 67 does correlate with grade and stage of the tumour thereby on prognostic significance. Hence ki 67 may be used as marker to predict aggressive behaviour of bladder neoplasms and also to differentiate high grade and low grade tumours.